DOI: 10.14264/uql.2017.504
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Structure and Functionality in Ruminants Fed the Probiotic Bacillus amyloliquefaciens H57

Abstract: In the agricultural industry, farmers are continually searching for ways to improve animal production. Developing a more efficient digestive system is one such way that this can be achieved.In domesticated ruminants such as sheep and cattle, the feed material is initially digested in the largest and most prominent compartment of the alimentary canal: the rumen. The rumen is populated by a complex community of microorganisms that are capable of degrading the tough fibrous components of the plant cell wall, rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 241 publications
(384 reference statements)
0
4
0
Order By: Relevance
“…Although not measured directly, a higher ruminal NH 3 concentration due to the H57 supplementation recorded in this study may be associated with higher proteolytic and deamination activities by ruminal bacteria. Schofield [ 29 ] found that feeding H57 pellets to pregnant ewes caused an increase in Prevotella spp. populations, which are generally major contributors to protein and peptide degradation in the rumen [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not measured directly, a higher ruminal NH 3 concentration due to the H57 supplementation recorded in this study may be associated with higher proteolytic and deamination activities by ruminal bacteria. Schofield [ 29 ] found that feeding H57 pellets to pregnant ewes caused an increase in Prevotella spp. populations, which are generally major contributors to protein and peptide degradation in the rumen [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The method used to prepare H57 inoculum for the cattle trial was as described by Schofield [ 29 ]. Briefly, the production of the H57 inoculum was performed in a series of batch cultures, then cultivated in a 100 L fermenter for the production of spores.…”
Section: Methodsmentioning
confidence: 99%
“…The un-inoculated pellets were produced prior to the H57 inoculated pellets. The procedure used to prepare the H57 inoculum for this experiment was as described by Schofield [ 26 ]. Briefly, the H57 inoculum was prepared in a 100 L fermenter at the University of Queensland and the bacterial spores and vegetative cells were subsequently separated from the supernatant in a Sharples Centrifuge AS26 at 2500 g (Sharples Separator Works, West Chester, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The method used to prepare H57 inoculum for the cattle trial was as described by Reference [ 17 ]. Briefly, the production of the H57 inoculum was performed in a series of batch cultures, then cultivated in a 100 L fermenter for the production of spores.…”
Section: Methodsmentioning
confidence: 99%